Monitoring a keystone species (Alosa pseudoharengus) with environmental effects: A comparison with direct capture and environmental DNA. - Matthew M Dougherty; Andrew MacDonald; Geneva York; David M Post (PLoS ONE)
Keystone species are important drivers of ecological processes. Their ecological importance makes them prime candidates for biological monitoring, both to preserve and restore their populations when facing decline, and to limit their spread as invasive species. To monitor species well requires cost and labor efficient methods that are capable of detecting the target species at low abundances. Traditional sampling methods, or methods of direct capture, can be labor intensive when trying to monitor large areas or species at low abundances. Another method, environmental DNA (eDNA), has emerged as a more cost and time efficient supplement to traditional monitoring methods. Environmental DNA techniques and strategies continue to be developed, but face limitations for some taxonomic groups within certain habitats. Here, we propose a novel method for monitoring keystone species: environmental effects sampling. Keystone species have large effects on their environment relative to their abundance. Measuring their environmental effects-or quantifiable changes in the biotic or abiotic environment due to organism-environment interactions-has potential as a low-effort and low-cost method for detecting keystone species. In this study, we compare the effectiveness of traditional sampling, eDNA methods, and environmental effects sampling as an alternative low cost and time efficient method for monitoring the presence and abundance of an ecologically important keystone species, the alewife, Alosa pseudoharengus, in freshwater lakes. The alewife is a zooplanktivorous fish managed as a species of conservation concern along coastal New England, USA, and an invasive or non-native species throughout the Laurentian Great Lakes watershed. We sampled lakes throughout Michigan and Connecticut from 2018-2020 and compared the three monitoring methods along four axes: alewife presence/absence, alewife abundance, financial cost, and time efficiency. Our results suggest that monitoring alewife with environmental effects is more accurate, more cost efficient, and more time efficient than purse seining and eDNA. Our environmental effects results also led to the discovery that two historically recognized alewife lakes no longer contained alewife, as confirmed by traditional sampling. However, environmental effects monitoring was only useful for determining alewife presence/absence, and was not reliable for determining alewife relative abundance. Environmental effects monitoring presents novel opportunities for efficiently and effectively monitoring keystone species such as alewife for the purpose of restoration or management.